Application and simulation of a prescribed burn in an oak-pine forest in Guerrero, México - López-López, Bernardo; Flores-Garnica, Jo´sé Germán; Aguirre-Calderón, Oscar Alberto; Silva-Aparicio, Marisa (Ecosistemas y Recursos Agropecuarios, 2024)
Standardized fuel models are a useful tool to predict fire behavior and propose forest fire suppression strategies. The aim was to compare the simulations of fire behavior with the result of a prescribed burn in an oak-pine forest in Guerrero, Mexico. Leaf litter (Ho), and mulch (Ma) samples were collected in 0.09 m2 at the end of the planar intersection lines for woody fuel sampling. The simulations in the FUEGO system were based on: a) field fuel loads, and b) theoretical loads of models 8 and 9. During the development of the burning, the temperature (T), relative humidity (HR), speed of the wind (VV), flame height (ALL) and fire spread speed (VP). The fuel load of 11 t ha-1 led to a PV = 1.07 m min-1 and ALL = 0.65 m for burning against the slope. The simulations with a mean square error (CME) of 0.11 showed acceptable values of ALL (0.54 and 0.64 m) except for the ALL-M8 model with 0.24 m (p < 0.05). The VP-real did not present statistical diferences with the simulations for values of 0.40 and 1.78 m with a CME = 0.54 and 1.56, the VP-9 and VP-M9 models provided high simulation values compared to the VP-M8 (p < 0.05). Fire behavior responded to changes in HR, VV and spatial distribution of fuels in the field.